The East Asian Subtropical Jet Stream and Atlantic tropical cyclones - Gabriele Villarini; Wei Zhang (Hydroshare, 2020)
Atlantic tropical cyclones (TCs) can cause significant societal and economic impacts, as 2019’s Dorian serves to remind us of these storms’ destructiveness. Decades of effort to understand and predict Atlantic TC activity have improved seasonal forecast skill, but large uncertainties still remain, in part due to an incomplete understanding of the drivers of TC variability. Here we identify an association between the East Asian Subtropical Jet Stream (EASJ) during July-October and the frequency of Atlantic TCs (wind speed ≥ 34 knot) and hurricanes (wind speed ≥ 64 knot) during August-November based on observations for 1980-2018. This strong association is tied to the impacts of EASJ on a stationary Rossby wave train emanating from East Asia and the tropical Pacific to the North Atlantic, leading to changes in vertical wind shear in the Atlantic Main Development Region (80°W-20°W, 10°N-20°N).